Efisiensi Empat Lembaga Amil Zakat (LAZ) Terbesar di Indonesia: Studi Komparatif Menggunakan Data Envelopment Analysis (DEA) - Abdullah Ahadish Shamad Muis; Mohammad Fausi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Zakat, Infaq, and Sadaqah (ZIS) fund management in Indonesia plays an important role in supporting the social and economic welfare of the community. However, the effectiveness and efficiency of ZIS fund management in Zakat Institutions (LAZ) remain challenging, particularly in ensuring that managed resources are optimized for the benefit of beneficiaries. This study aims to analyze the efficiency of ZIS fund management in the four largest LAZs in Indonesia using the Data Envelopment Analysis (DEA) approach. DEA was chosen as the analytical method due to its ability to measure relative efficiency among Decision-Making Units (DMUs) with similar objectives. Using secondary data from the Annual Reports of Indonesia's four largest LAZs—LAZ Rumah Zakat Indonesia, LAZ Muhammadiyah (LAZISMU), LAZ Nahdhatul Ulama (LAZISNU), and LAZ Dompet Dhuafa Republika—for the years 2020-2022, specifically on ZIS funds collected, fixed assets, salaries and allowances, ZIS distribution, and operational costs, this study found variations in the efficiency levels of fund management among the four LAZs examined. In 2021 and 2022, LAZ Rumah Zakat Indonesia recorded inefficiency with scores of 73.3% and 89.9%, respectively. LAZ Muhammadiyah (LAZISMU) experienced even worse things, in the same years it experienced inefficiency with scores of 31.8% and 32.5%. Similarly, LAZ Dompet Dhuafa Republika recorded inefficiency with a score of 38.8% in 2022. Only LAZ Nahdhatul Ulama (LAZISNU) consistently achieved a 100% efficiency score from 2020 to 2022. The findings of this study are expected to provide recommendations for related LAZs to review their fund management strategies in order to optimize performance, offer insights for policymakers to strengthen regulations and promote transparency in ZIS fund management, and serve as a recommendation for muzakki to select LAZs that are efficient and transparent, thereby ensuring that their contributions are utilized optimally.